The integrated application of music intervention in clinical practice for cancer patients - Fan Zhang; Xinyang Li; Junyan Wang; Minting Ma; Yu Xu; Lei Hong (Holistic Integrative Oncology, 2026)
Abstract Objective In recent years, the incidence of malignant tumors has continued to rise, making it the second leading cause of death and posing significant physical and psychological impacts on patients' health. Studies have shown that music intervention has a positive effect on alleviating emotions, improving symptoms, and enhancing the quality of life in cancer patients. The purpose of this review is to explore the application of music intervention in clinical practice for malignant tumor patients by summarizing existing literature. Methods Chinese and English databases, including CNKI, Wanfang Database, PubMed, FMRS, and Web of Science, were searched to comprehensively collect relevant studies on the effects of music intervention on the psychological and physical symptoms, as well as rehabilitation, of malignant tumor patients. The search was conducted up until July 2024. Results The majority of research findings indicate that music intervention has a positive effect on improving cognitive function, alleviating negative emotions, reducing chemotherapy side effects, relieving pain, and enhancing sleep quality in cancer patients. Conclusion Music intervention is a simple, safe, and effective adjunctive treatment modality that can be used in clinical practice to improve psychological distress, alleviate physical symptoms, and facilitate postoperative rehabilitation in cancer patients. It is worthy of promotion in clinical settings.